The Copyright Infringement In Cinematography - Putri Andini (Universitas Internasional Batam, 2018)
The drama entitled “Kau Yang Berasal Dari Bintang” produced by SinemArt and aired by RCTI TV station on 28 April 2014 was claimed as a plagiarism of the most popular South Korean drama